Manganese doped Ni-MOF derived porous carbon-based bifunctional oxygen electrode catalyst for metal air batteries - Iqbal, Naseem; Ahmad, Rabia; Noor, Tayyaba; Shahzad, Nadia; Shahzad, Muhammad Imran (Materials chemistry and physics, 2025)
In recent times, bimetallic electrocatalysts have been the subject of extensive research owing to their exceptional electrical configuration, synergistic impact, and remarkable efficacy in charge transfer. A bifunctional catalyst, consisting of a Mn-doped Ni-based metal-organic framework (MOF) embedded in porous carbon, was synthesized by a simple hydrothermal process using terephthalic acid as an organic linker. The obtained material was subjected to pyrolysis and was evaluated for its use in metal-air batteries. The atomic and molecular structures of pure MOFs and Mn-doped Ni-MOFs were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and energy dispersive spectroscopy (EDS). Post pyrolysis, the examination unveiled an ideal porosity configuration, leading to the highest specific surface area. Both the oxygen evaluation reaction (OER) and the oxygen reduction reaction (ORR) were run as tests to see how well the electrocatalysts might work. The Mn2.5Ni2.5-PC catalyst demonstrated better performance compared to pure MOFs and bimetallic MOFs, with an onset potential of 0.83 V and a half-wave potential of 0.74 V. In addition, the substance exhibited a low overpotential of 343 mV at a current density of 10 mA/cm2 in the oxygen evolution process. The Tafel slope, which measures the reaction rate, was determined to be 64.21 mV/dec. These results are in line with those seen in the original MOFs. The ultimate altered bimetallic electrocatalyst exhibited exceptional durability, with chronoamperometry lasting for 7500 s and cyclic voltammetry for 2000 cycles. The remarkable outcomes showcased the capabilities of these innovative MOFs for application in rechargeable Zn-air batteries. •Analysis of Mn-doped Ni-MOFs shows an optimal porous structure, yielding the largest specific surface area.•Electrocatalysts were tested for their ability to facilitate the oxygen evolution (OER) and reduction (ORR) reactions.•The Mn2.5Ni2.5-PC catalyst outperformed pure and bimetallic MOFs, with onset and half-wave potentials of 0.83 V and 0.74 V.•The material showed a low overpotential of 343 mV at 10 mA/cm² and a Tafel slope of 64.21 mV/dec in OER, matching parent MOFs.•The modified bimetallic electrocatalyst showed excellent stability, with 7500s chronoamperometry and 2000 cycles of CV.